2023
DOI: 10.1108/oir-08-2021-0423
|View full text |Cite
|
Sign up to set email alerts
|

Data sharing and reuse practices: disciplinary differences and improvements needed

Abstract: PurposeThis study investigates differences and commonalities in data production, sharing and reuse across the widest range of disciplines yet and identifies types of improvements needed to promote data sharing and reuse.Design/methodology/approachThe first authors of randomly selected publications from 2018 to 2019 in 20 Scopus disciplines were surveyed for their beliefs and experiences about data sharing and reuse.FindingsFrom the 3,257 survey responses, data sharing and reuse are still increasing but not ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 52 publications
1
14
1
Order By: Relevance
“…If researchers perceive that sharing their data is a norm valued by their peers, they are more likely to participate in open science initiatives. Conversely, the transition to open science can be more challenging if the prevailing culture doesn't prioritise transparency or if there's a perceived norm against data sharing [47]. Several studies from the review that have also indicated culture and perceived norms as factors motivating open science practice through research data sharing and reuse are presented in Table 6 below.…”
Section: Culture and Perceived Normsmentioning
confidence: 99%
“…If researchers perceive that sharing their data is a norm valued by their peers, they are more likely to participate in open science initiatives. Conversely, the transition to open science can be more challenging if the prevailing culture doesn't prioritise transparency or if there's a perceived norm against data sharing [47]. Several studies from the review that have also indicated culture and perceived norms as factors motivating open science practice through research data sharing and reuse are presented in Table 6 below.…”
Section: Culture and Perceived Normsmentioning
confidence: 99%
“…If researchers perceive that sharing their data is a norm valued by their peers, they are more likely to participate in open science initiatives. Conversely, the transition to open science can be more challenging if the prevailing culture doesn't prioritize transparency or if there's a perceived norm against data sharing (Khan et al, 2023). Several studies from the review that have also indicated culture and perceived norms as factors motivating open science practice through research data sharing and reuse are presented in Table 2.6 below.…”
Section: Culture and Perceived Normsmentioning
confidence: 99%
“…For example, the FAIR (Findable, Accessible, Interoperable, and Reusable) data principles provide a framework for ensuring that data are shared in a way i.e. easily discoverable, accessible, and reusable [ 52 , 53 ]. To support this initiative, data reporting templates are being established with a purpose of setting common standards and practices for data sharing and description , so researchers can promote more efficient and effective data sharing and reuse across different domains and disciplines.…”
Section: Reusability Of Data: General Principlesmentioning
confidence: 99%